Nocturnal sleep pattern in native Brazilian Terena adults - RUBENS REIMÃO; JOSÉ CARLOS SOUZA; CARLOS EDUARDO VILELA GAUDIOSO; HELLEN DA COSTA GUERRA; ANDREA DAS CHAGAS ALVES; JOLENE CRISTINA FERREIRA OLIVEIRA; NILTON CEZAR ANTONIO GNOBIE; DESIRÉE CORREA GUERRA SILVÉRIO (Arquivos de Neuro-Psiquiatria)
Social-economic factors influence sleep habits. This research analyzes characteristics of nocturnal sleep in Brazilian Native Terena adults. Sixty-four adults (31 M; 33 F) from 18 to 75 years, with a mean age of 37.0, from the Indian Reservation village of Córrego do Meio, in the central region of Mato Grosso do Sul, an agriculturally oriented group were evaluated. Nocturnal sleep characteristics were evaluated by means of a standard questionnaire applied to each individual. It was observed that reported nocturnal sleep was longer, sleep onset was earlier and wake up time was also earlier than usually described in urban populations. The mean total time in bed was 8.5 h or more, in every age bracket. The seven-day prevalence rate of insomnia was 4.6%, while the seven-day prevalence rate of hypnotic use was 1.5%, both remarkably less than described in urban populations. These findings stress the need to consider ethnic influences on sleep patterns and disorders.